2013
DOI: 10.1103/physreve.88.022506
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic light scattering and viscosity measurements in a ternary and quaternary discotic lyotropic nematic liquid crystal: Tuning the backflow with salt

Abstract: Using a dynamic light scattering technique, we measure the damping rate of thermal fluctuations of the nematic director for the so-called disklike nematic N(D) phase of both the ternary lyotropic K-laurate-1-decanol-H(2)O system and the quaternary one of similar composition except for the addition of salt (K(2)SO(4)). By varying the scattering angle in suitable geometries and polarizations, we are able to measure the orientational diffusivities associated with the pure deformations of splay and twist. A previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…One could imagine that this assumption eventually breaks down in the case of quaternary samples, as the dramatic increase of η observed there might be associated to an increase of the micelle size, e.g., because of salt-mediated hydration (Figueiredo Neto and Salinas 2005;Galerne et al 1987). However, recent DLS data (Risi et al 2013) have shown a giant backflow effect in these salted mixtures, which implies that γ 1 (N D ) η holds for such systems too. A similar comparison can be made in the ternary N C phase, for which we can quote the DLS result (Lacerda Santos and Amato 1999) D twist = 0.42×10 −12 m 2 /s.…”
Section: Rotational Viscosities Of Nearby Lyotropic Mixturesmentioning
confidence: 91%
“…One could imagine that this assumption eventually breaks down in the case of quaternary samples, as the dramatic increase of η observed there might be associated to an increase of the micelle size, e.g., because of salt-mediated hydration (Figueiredo Neto and Salinas 2005;Galerne et al 1987). However, recent DLS data (Risi et al 2013) have shown a giant backflow effect in these salted mixtures, which implies that γ 1 (N D ) η holds for such systems too. A similar comparison can be made in the ternary N C phase, for which we can quote the DLS result (Lacerda Santos and Amato 1999) D twist = 0.42×10 −12 m 2 /s.…”
Section: Rotational Viscosities Of Nearby Lyotropic Mixturesmentioning
confidence: 91%
“…The viscosity η splay is the largest in the N C phase of chromonic DSCG, whereas in the micellar N D phase η bend is the largest. The reverse behaviour of N C and N D phases regarding η splay vs. η bend can be explained according to the Ericksen-Leslie model with the backflow mechanism [61][62][63][64][65][66][67][68][69]. It seems that backflow lowers η splay but not η bend in lyotropic N D phases.…”
Section: Extremely Small Twist Elastic Constants In Lyotropic Nematic Lcsmentioning
confidence: 99%